Assembling the Assembler: Reanimating the "Lost" Motion Machine of Wachsmann, Bollinger, and Mendoza. Issue 1 (2nd January 2022) - Andrzejewski, Elizabeth; Shaffer, Marcus; Obonyo, Esther
Abstract : In the late 1960s, Konrad Wachsmann moved to the University of Southern California to begin the Building Research Institute, a multidisciplinary studio and laboratory dedicated to reimagining building construction through a universal comprehensiveness— one that considered politics, science, social science, economics, and technologies in relation to industrial architecture. While at USC, Wachsmann and his students developed the Location Orientation Manipulator (LOM), an architecture machine "for the control, measurement, and display of the kinematics of (building) design and assembly" (Ward Jr. 1972). This paper examines the LOM as a 'universal building machine' designed by architects for industrialized architecture and details a digital reconstruction/reanimation of the LOM using Autodesk Fusion software. The authors speculate there are mechanical qualities related to building automation and specific to architecture within the unarticulated history of the LOM. These characteristics may inform and enhance contemporary architectural technologies.